Relationships of mental budgeting of the self-employed without personnel with tax compliance, pension, and disability arrangements - Antonides, Gerrit; de Groot, I. Manon (Frontiers in Behavioral Economics, 2024)
Introduction Self-employed people without personnel mostly behave like consumers in managing their business finances, frequently leading to ill-management of the company finances. Ill-management may lead to inability to fulfill important financial obligations and making financial arrangements for the future. Here, we investigate the hypothesis that financial management is related to tax compliance. Methods We use having an overview of expenses, making ends meet, occurrence of a business bank overdraft, and how long the business could survive without income, as indicators of financial management. Four measures of tax compliance, i.e., the OECD measure of tax compliance, measures taken by the tax administration, enforced tax compliance, and voluntary tax compliance, and two measures of social security, i.e., pension and disability arrangements, are included. We use survey data from a sample of 1,191 Dutch self-employed people without personnel, roughly equally divided between starters ( ≤ 3 years in business) and non-starters (>3 years in business). Results We found both significant direct and indirect effects of mental budgeting on tax compliance and social security arrangements, thus showing incomplete mediation effects of financial management. Discussion The mediation effects of having an overview of expenses were relatively strong for the OECD and voluntary compliance measures, whereas the mediation effects of not making ends meet and bank overdrafts were relatively strong for measures taken by the tax administration and enforced compliance, thus indicating different financial management processes matching different motivations of tax compliance.